Duverger's law and the meaning of Canadian exceptionalism - Gaines, Brian J. (1999)
Duverger's law is an unusually simple and specific elaboration on exactly how political institutions "matter": It proposes that plurality rule elections result in two-party competition. Canada is commonly thought to violate the law at the national level, but to match its predictions at the district level, and thus not to constitute a genuine counterexample. In fact, analysis of a vast data set of Canadian election returns reveals that these elections are multicandidate events, district by district, year after year. An explanation for this multipartyism may lie in the complicating factor of federalism, because Canadian provinces often feature strikingly different national and provincial party systems. Generally, the Canadian case illustrates that theories relating party systems to electoral law but not to other institutions are unrealistically parsimonious. - Reproduced
Keywords: Duverger, Maurice; Politics and government